Клінічні ознаки нестабільності зв’язкового апарата кришталика - Завгородня, Наталія Григорівна; Саржевський, Андрій Сергійович; Zavgorodnja, N. G.; Sarzhevsky, A. S. (My University, 2016)
Мета роботи. Визначення клінічних діагностичних критеріїв нестабільності зв’язково-капсульного апарата кришталика. Обстежено 583 пацієнта (618 очей) з катарактою, вік від 38 до 89 років, 285 жінок (48,9%) і 298 чоловіків (51,1%). Вивчено клінічні ознаки нестабільності зв’язкового апарата кришталика. Встановлено, що серед анамнестичних даних чинниками ризику розвитку ускладнень є травма ока (92,9%), раніше перенесені оперативні втручання (81,6%), глаукома (67,2%), черепно-мозкова травма (58,3%), міопія високого ступеня (57,6%), похилий вік пацієнтів (21,8%). Серед чинників ризику розвитку підвивиху кришталика переважали неможливість досягнення достатнього мідріазу при інстиляції мідриатиків (65,3%), зміни переднього відділу ока на тлі псевдоексфоліативного синдрому (67,3%), наявність факодонезу (22,5%), іридодонезу (39,7%). Серед інтраопераційних ознак переважали складки передньої капсули (41,8%) і флюктуація кришталика (93,9%) при виконанні капсулорексису. Introduction. Defi nition of the presence of lens’ subluxation before operation, or in the early stages of operation can prevent a number of intraoperative complications, help the surgeon to choose the best tactic for this situation. These symptoms can be rather subjective and can depend on the doctor’s care and experience. Very often the symptoms of ligaments lens instability aren’t diagnosed during the initial examination, and they are manifested in the form of complications during surgery. The purpose was to increase the effectiveness of phacoemulsifi cation cataract with zonular ligament damage based on clinical diagnostic criteria of lens subluxation. Material and methods. There are the results of clinical ophthalmology research of 583 patients (618 eyes) aged 38 – 89 years, operated on cataract in the Eye Microsurgery Department Clinical Hospital N3. Among them there were 298 men (51,1%) and 285 women (48,9%). Cataract was diagnosed from the initial stage to overripe cataract, 38 eyes (6,2%) – the initial cataract, 45 (7,3%) – immature, in 362 eyes (58,5%) – almost mature, 138 – mature (22,3%), 35 (5,7%) – hypermature cataracts. According to lens density (classifi cation Buratto) patients were divided into: 2–3st – in 278 eyes (45%), 4st – 266 eyes (43%), 5st – 74 eyes (12%). Researches were carried out in several successive stages: careful history; defi nition lens subluxation symptoms before surgery and during surgery. According to the analysis of the data set groups of patients were formed. The fi rst group consisted of 97 patients (98 eyes) with the lens subluxation cataract, second – 486 patients (520 eyes) without lens subluxation cataract.
Clinical signs of lens zonular weakness
Keywords: клінічні ознаки; підвивих кришталика; факоемульсифікація катаракти; clinical signs; lens subluxation; phacoemulsifi cation of cataract